Nicotine Dependence and Smoking Habits of Hungarian Police Cadets - Ákos Erdős (Belügyi Szemle, 2025)
Aim: Smoking is one of the most significant health risk factors. Some studies have shown that the prevalence of smoking is higher in some professions (e.g. police personnal) than in the general population. The aim of the research presented in this study is to investigate the smoking habits and nicotine dependence of Hungarian trainee police officers (so-called police cadets).